Non-medical prescribing in New Zealand: an overview of prescribing rights, service delivery models and training. (November 2017) - Raghunandan, Rakhee; Tordoff, June; Smith, Alesha
Aim: In this paper, we aim to provide an updated source of information for nonmedical prescribing (NMP) in New Zealand (NZ). Methods: A variety of NZ sources were used to collect data: legislation, policy documents and information from professional and regulatory organizations, and education providers. Results: In NZ, the legal categories for prescribers include authorized, designated, and delegated prescribers. Authorized prescribers include dentists, midwives, nurse practitioners, and optometrist prescribers. Designated prescribers include pharmacist prescribers, registered nurse prescribers, and dietitian prescribers. There are no delegated prescribers in NZ at this time. There is variation in the regulation, educational programmes and prescribing competencies used by the different prescribing health professionals involved in NMP in NZ. Conclusion: This update collates relevant information relating to NMP in NZ into one consolidated document and provides policy makers with a current overview of prescribing rights, service delivery models, training requirements, and prescribing competencies used for NMP in NZ. As NMP in NZ continues to expand and evolve, this paper will form a baseline for future NMP research in NZ. NZ needs to develop overarching NMP policy to enable consistency in the various aspects of NMP, thereby delivering a safe and sustainable NMP service in NZ.